2018
DOI: 10.1177/0003702818812144
|View full text |Cite
|
Sign up to set email alerts
|

A Two Components Approach for Long Range Remote Raman and Laser-Induced Breakdown (LIBS) Spectroscopy Using Low Laser Pulse Energy

Abstract: The remote detection of chemicals using remote Raman spectroscopy and laser-induced breakdown spectroscopy (LIBS) is highly desirable for homeland security and NASA planetary exploration programs. We recently demonstrated Raman spectra with high signal-to-noise ratio of various materials from a 430 m distance during daylight with detection times of 1–10 s, utilizing a 203 mm diameter telescopic remote Raman system and 100 mJ/pulse laser energy at 532 nm for excitation. In this research effort, we describe a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Because the two techniques use a similar instrumental architecture based on the same principal components (a laser, a spectrometer and a detector), several combined LIBS-Raman customized setups have been elaborated. Some setups were designed for analysis at the microscale [1,2] while other setups were developed for remote analysis [3][4][5][6][7][8] in particular for field measurements. Notably, most of these instruments were developed with the motivation of designing a compact LIBS-Raman instrument for future planetary exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Because the two techniques use a similar instrumental architecture based on the same principal components (a laser, a spectrometer and a detector), several combined LIBS-Raman customized setups have been elaborated. Some setups were designed for analysis at the microscale [1,2] while other setups were developed for remote analysis [3][4][5][6][7][8] in particular for field measurements. Notably, most of these instruments were developed with the motivation of designing a compact LIBS-Raman instrument for future planetary exploration.…”
Section: Introductionmentioning
confidence: 99%
“…The remote detection of chemicals using laser-based techniques is highly desirable due to increasing planetary exploration activities and anti-terrorism government programs for detecting hazardous chemicals [1][2][3][4]. Remote Raman systems, consisting of an active pulsed laser and a gated detector provide rapid and reliable detection and identification of chemicals, via gating the pulsed Raman echoes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the unique advantages of Raman spectroscopy, stand-off Raman spectroscopy was initially developed by Angel et al for the detection of K 4 [Fe­(CN) 6 ], NaNO 2 , NaNO 3 , and CCl 4 at 17 m in 1992 . After 2000, time-gating techniques and telescopes have been applied in remote detection technology, which greatly enhanced the capability of remote Raman detection. Until now, the reported farthest distance of remote Raman detection is 1752 m, which used a telescope of 203 mm diameter and a 532 nm pulsed laser for the explosive detection of nitrobenzene, potassium chlorate, and ammonium nitrate . Previously, Bobrovnikov et al reported the trace Raman detection of TNT with a concentration of 0.5 μg/cm 2 from a 10 m distance, which is the lowest concentration that has ever been reported for remote Raman detection of explosives .…”
Section: Introductionmentioning
confidence: 99%